Pengaruh Terapi Murottal Al-Qur’an Terhadap Tingkat Kecemasan Ibu Hamil Primigravida Trimester III dalam Menghadapi Persalinan - Ainah, Ainah; Zakiah, Zakiah; Hapisah, Hapisah; Megawati, Megawati (Midwifery Departement Poltekkes Kemenkes Banjarmasin, 2024)
Introduction: Pregnancy is a natural process in a woman's life which is characterized by physical and psychological changes. These changes make pregnant women experience anxiety, especially primigravida pregnant women in the third trimester. According to data from the Ministry of Health of the Republic of Indonesia 2018 and the Ministry of Health of the Republic of Indonesia 2020, there has been an increase in the anxiety of pregnant women by 20% for 2 years. Anxiety reduction can be done with murottal al-qur'an therapy. Purpose: The aim of this study to determine the effect of murottal Al-Qur'an therapy on anxiety in third trimester pregnant women. Methods: This research uses quantitative research with a quasi-experiment using the nonequivalent control group research design. The population in this study was 22 respondents taken using total sampling technique. The independent variable in this study was murottal Al-Qur'an therapy. The dependent variable in this research is anxiety, data collection used the HRS-A questionnaire. Data analysis used the independent t testResults: The results of the study showed that there was an effect of providing murottal Al-Qur'an therapy and relaxation therapy on anxiety in third trimester pregnant women (murottal therapy = 0.018, relaxation therapy= 0.001). Conclusion: The resulting effect is a decrease in the anxiety level of pregnant women after being given murottal Al-Qur'an therapy and relaxation therapy. Therefore, midwives at community health centers can socialize murottal Al-Qur'an therapy and relaxation therapy to provide calm benefits and reduce anxiety in pregnant womenKeyword : anxiety, murottal al-qur’an, pregnancy, relaxation